Family Functioning and the Course of Adolescent Bipolar Disorder - Sullivan, A; Judd, C; Axelson, D; Miklowitz, D (2012)
The symptoms of bipolar disorder affect and are affected by the functioning of family environments. Little is known, however, about the stability of family functioning among youth with bipolar disorder as they cycle in and out of mood episodes. This study examined family functioning and its relationship to symptoms of adolescent bipolar disorder, using longitudinal measures of family cohesion, adaptability, and conflict. Parent- and adolescent-reported symptom and family functioning data were collected from 58 families of adolescents with bipolar disorder (mean age =14.48 ± 1.60; 33 female, 25 male) who participated in a 2-year randomized trial of family-focused treatment for adolescents (FFT-A). Cohesion and adaptability scores did not significantly change over the course of the study. Parent-reported conflict prior to psychosocial treatment moderated the treatment responses of families, such that high-conflict families participating in FFT-A demonstrated greater reductions in conflict over time than low-conflict families. Moreover, adolescent mania symptoms improved more rapidly in low-conflict than in high-conflict families. For all respondents, cohesion, adaptability, and conflict were longitudinally correlated with adolescents' depression scores. Finally, decreases in parent-reported conflict also predicted decreases in adolescents' manic symptoms over the 2-year study. Findings suggest that family cohesion, adaptability, and conflict may be useful predictors of the course of adolescent mood symptoms. Family conflict may be an important target for family intervention in early onset bipolar disorder. © 2012.